What it means to be a woman in the field of biomedical informatics: exploring the lived experiences of women managers in the kingdom of Saudi Arabia. (27th October 2020) - Aldekhyyel, Raniah N; Almulhem, Jwaher A; Binkheder, Samar; Muaygil, Ruaim A; Aldekhyyel, Shahad N
Abstract: Objective: Although women in the field of biomedical informatics (BMI) are part of a golden era, little is known about their lived experiences as informaticians. Guided by feminist standpoint theory, this study aims to understand the impact of social change in the Kingdom of Saudi Arabia- in the form of new policies supporting women and health technological advancements—in the field of BMI and its women informaticians. Materials and Methods: We conducted semistructured telephone interviews with 7 women managers in the field of BMI, identified through LinkedIn. We analyzed interview transcripts to generate themes about their lived experiences, how they perceived health information technology tools, identified challenges that may hinder the advancement of the field, and explored the future of BMI from their perspectives. During our analysis, we utilized a feminist theoretical approach. Results: Women managers in the field of BMI shared similar experiences and perspectives. Our analysis generated 10 themes: (1) career beginning, (2) opportunities given, (3) career achievements, (4) gender-based experiences, (5) meaning of BMI, (6) meaning of health information technology tools, (7) challenges, (8) overcoming challenges, (9) future and hopes, and (10) meaning of "2030 Saudi vision." Early in their careers, participants experienced limited opportunities and misperceptions in understanding what the field of informatics represents. Participants did not feel that gender was an issue, despite what feminist theory would have predicted. Conclusions: Recognizing the lived experiences of women in the field of BMI contributes to our collective understanding of how these experiences may enhance our knowledge of the field.